Guerre e conflitti, etnie e nazioni - Raspa, Venanzio (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2018)
The theses exposed by Alexius Meinong in two newspaper articles in 1873 are taken as the paradigm of a feeling that was common to young Austrian intelligentsia. Meinong upholds a conception of life as struggle and of history as a series of struggles among nations. In his view, the defence of the interests of a people is absolute and generates conflicts among nations that will increasingly dominate future scenarios. The concept of nation has an identification function inward and one of dissociation outward. This discourse is contextualised within the framework of the various student corporations of the University of Vienna, where the new ruling class was forming which, despite different political ideas, was united by nationalism. Finally, the paper analyses the opposing views of Eric J. Hobsbawm and Anthony D. Smith on the idea of nation and suggests some similarities between the Habsburg Empire and the European Union. Keywords: War; Nation; Nationalism; Austrian history and philosophy; Meinong.